PEMBERDAYAAN SUMBER DAYA LINGKUNGAN MELALUI MANAJEMEN SAMPAH (MaPah) DI DESA CIASEM TENGAH, DUSUN WANAJAYA RT 18/19 dan RW 05 - Azizah, Nur; Nisa Fadlila Rahma; Rahmad Riski Mulya (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Field Work Lecture (KKN) is the implementation of the Tri Dharma of Higher Education in the aspect of service. Students go down to the community and do community service. Through community service activities in Ciasem Tengah Village, precisely in Dusun Wanajaya, there is a synergy between the university and the community as a form of SISDAMAS (Community Empowerment System). There is a synergy between universities and the community as a form of SISDAMAS (Community Empowerment System). The purpose of this service is that through this community empowerment-based program it is hoped that it can strengthen and maximize the potential of the community and the rural environment for the realization of sustainable programs in the community.